STUDY OF COMMON FIXED POINT RESULT OF PAIR OF SELF MAPS IN G-METRIC SPACE - V.V., Latpate (International journal of advanced research (Indore), 2023)
In this article we study weakly compatible maps and proved common fixed point theorem of weakly compatible mappings in Generalized Metric space. AMS Subject classification:-47H10,47H09.